Application of vernacular architectural ideas in New Saffein Village of Kish Island - Afshar, Ali; Salleh, Elias; Abdullah, John Ashraf Lucas (Universiti Putra Malaysia Press, 2011)
The vernacular architecture of Iran is a result of a long time process of both social and cultural developments which have expanded all over the country. The hot and humid region of Iran is situated in a long and thin coastal strip on the northern side of the Persian Gulf. Kish Island, with more than 1000 years of history, is located in this region with the same social and climatic factors. Kish was selected as the first Free Tourist Zone of the country in 1971. Following this, Masheh, the most flourishing village on the Island at that time, was relocated in an area adjacent to Old Saffein village, on the north-west coast. This new village is called New Saffein. It has a mixture of traditional and modern architecture. This study sought to emphasize the architectural concepts and ideas which are applied in the houses of New Saffein. The study also reviewed the background of the island in field of vernacular architecture through documental and observational studies. It also investigated the architecture of New Saffein in Kish as a case study in comparison with the vernacular architecture in Old Saffein. It will review the design and construction processes of the houses in New Saffein in relation to the traditional methods used in Kish Island. The article finally attempts to analyse the application of vernacular knowledge in designing New Saffein village to find strategies for guiding the process of developing contemporary housing appropriate for Kish Island and other similar places.